Impact of different processing techniques on reduction in oil content in deep-fried donuts when using kombucha cellulose hydrolysates - He, Shan; Zhang, Yang; Gu, Caiqing; Wu, Yixiao; Farooq, Muhammad Adil; Young, David James; Wong, Jonathan Woon Chung; Chang, Kun; Tian, Bin; Kumari, Ankita; Rahaman, Abdul; Gao, Jingrong (Frontiers in Sustainable Food Systems, 2022)
To evaluate the efficiency of the oil-reducing properties of kombucha cellulose, enzymolysis and microwave-assisted enzymolysis methods were developed. The water-holding capacity of the kombucha cellulose hydrolysates formed by these two methods was higher than for the intact kombucha cellulose, while the oil-holding capacity was lower. The hydrolysates of kombucha cellulose and the intact kombucha cellulose were used to make deep-fried donuts. During this process, kombucha cellulose hydrolysates were added instead of 2% flour, and from the results, the oil content of the donut decreased significantly from 28 to 15%, and the reduction was not related to the processing of the donut. The hardness and brittleness of all samples showed no significant change, and these samples had similar internal micro-structures, confirming texture profile analysis. In vitro digestion results suggested that there would be no adverse health effects from substituting kombucha cellulose hydrolysates in the deep-fried donut formula.